FINTECH MANAGEMENT IN ISLAMIC BANKING: SOLUTIONS AND CHALLENGES - Fitrahadi, Agung; Juanda, Ekhwan; Larasati, Febita Putri; Rani, Rani; Yulitasari, Sella (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
The advancement of information technology, particularly in the context of computers and the internet, has had a significant impact on the banking sector, including Islamic banking. This technology facilitates the integration and digitalization of banking services, such as e-banking, mobile banking, and fintech, enabling Islamic banking to expand access, enhance efficiency, and offer services that better align with Sharia principles. However, the implementation of technology in Islamic banking faces specific challenges, such as ensuring compliance with Sharia principles, maintaining information security, and addressing limitations in financial literacy among the public. To maximize the benefits of technology, Islamic banks need to consistently evaluate and ensure that the technology used adheres to Sharia principles, invest in cybersecurity solutions, improve financial literacy among the public, and establish partnerships with fintech companies that comply with Sharia regulations. By taking these steps, Islamic banking can effectively leverage technology to achieve sustainable growth and succes Keywords: Technology, Fintech, Islamic Banking